2011
DOI: 10.1002/cncr.26168
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin synthase expression and epigenetic regulation in nonsmall cell lung cancer

Abstract: BACKGROUND: Prostacyclin synthase (PGIS) metabolizes prostaglandin H(2), into prostacyclin. This study aimed to determine the expression profile of PGIS in nonsmall cell lung cancer (NSCLC) and examine potential mechanisms involved in PGIS regulation. METHODS: PGIS expression was examined in human NSCLC and matched controls by reverse transcriptase polymerase chain reaction (RT-PCR), Western analysis, and immunohistochemistry. A 204-patient NSCLC tissue microarray was stained for PGIS and cyclooxygenase 2 (COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…However, we also observed a significant increase in a protein which has the correct expected size for IL-23A (20 kDa). These results indicate that post-translational regulation of protein may also be occurring, similar to effects we previously observed for prostacyclin synthase in NSCLC [32]. In this regard IL-23A may be post-translationally modified upon maturation, in a manner similar to IL-6, and IL-12 where glycosylation is a frequent event [33].…”
Section: Discussionsupporting
confidence: 65%
“…However, we also observed a significant increase in a protein which has the correct expected size for IL-23A (20 kDa). These results indicate that post-translational regulation of protein may also be occurring, similar to effects we previously observed for prostacyclin synthase in NSCLC [32]. In this regard IL-23A may be post-translationally modified upon maturation, in a manner similar to IL-6, and IL-12 where glycosylation is a frequent event [33].…”
Section: Discussionsupporting
confidence: 65%
“…These findings raise the issue that HDACi may have potentially 'good' and 'bad' effects within the autoimmune disease setting, particularly with regard to pro-inflammatory cytokines. However, we and others have also shown that epigenetic targeting agents have the ability to affect the stability of both expressed mRNAs and proteins [80], and this effect has also been observed in RA, in which HDACi significantly reduced the stability of IL-6 mRNA in FLSs and macrophages [81]. …”
Section: Epigenetic Targeting Agents and Rheumatic Diseasementioning
confidence: 90%
“…For example, ceramide leads to apoptosis whereas sphingosine-1-phosphate leads to cell survival [Gatt and Dagan 2012]. Prostaglandin I2 is a metabolite of the arachidonic acid pathway and high levels of prostaglandins were reported in peritoneal fluids of endometriosis patients [Cathcart et al 2011;Meresman and Olivares 2012]. Selenomethionine has been identified as a probable agent that can be used in prostate cancers to inhibit, delay, or reverse carcinogenesis [Nyman et al 2004].…”
Section: Metabolic Signatures: Reporter Metabolitesmentioning
confidence: 98%